The role of ventricular–arterial coupling in cardiac disease and heart failure: assessment, clinical implications and therapeutic interventions. A consensus document of the European Society of Cardiology Working Group on Aorta & Peripheral Vascular Diseases, European Association of Cardiovascular Imaging, and Heart Failure Association. (12th March 2019) - Ikonomidis, Ignatios; Aboyans, Victor; Blacher, Jacque; Brodmann, Marianne; Brutsaert, Dirk L.; Chirinos, Julio A.; De Carlo, Marco; Delgado, Victoria; Lancellotti, Patrizio; Lekakis, John; Mohty, Dania; Nihoyannopoulos, Petros; et al.
Abstract : Ventricular–arterial coupling (VAC) plays a major role in the physiology of cardiac and aortic mechanics, as well as in the pathophysiology of cardiac disease. VAC assessment possesses independent diagnostic and prognostic value and may be used to refine riskstratification and monitor therapeutic interventions. Traditionally, VAC is assessed by the non‐invasive measurement of the ratio of arterial (Ea) to ventricular end‐systolic elastance (Ees). With disease progression, both Ea and Ees may become abnormal and the Ea/Ees ratio may approximate its normal values. Therefore, the measurement of each component of this ratio or of novel more sensitive markers of myocardial (e.g. global longitudinal strain) and arterial function (e.g. pulse wave velocity) may better characterize VAC. In valvular heart disease, systemic arterial compliance and valvulo–arterial impedance have an established diagnostic and prognostic value and may monitor the effects of valve replacement on vascular and cardiac function. Treatment guided to improve VAC through improvement of both or each one of its components may delay incidence of heart failure and possibly improve prognosis in heart failure. In this consensus document, we describe the pathophysiology, the methods of assessment as well as the clinical implications of VAC in cardiac diseases and heart failure. Finally, we focus on interventions that may improve VAC and thus modify prognosis.